The Effect of Spelling Bee Games to Students’ Vocabulary Mastery - Gisckha Hazezlima Aniza; Wulan Wangi; Wageyono (LUNAR, 2021)
The objective of the research was to know the effect of Spelling Bee game to students vocabulary mastery. This research design was in experimental research. The researcher observed 33 students’ of tenth grade TKJ 2 at SMK NU Mamba’ul Huda. The researcher used pre-test and post-test and those were in the form of multiple choice tests. The data were analyzed statistically by using T-test. Afterward, T-test was analyzed and interpreted with the degree of significances 5% with db = N – 1 = 33-1 = 32 and the T- table is 2,036. The results of T-test analysis was 12,09. The result showed that there was a significant difference between using and without spelling bee game to students vocabulary mastery. Based on the research result, it can be concluded that teaching English vocabulary by Spelling Bee game was effective and gave remarkable progress in students vocabulary mastery, especially in X TKJ 2 at SMK NU Mambaba’ul Huda Tegalsari.